Does Social Networking among Blood Donors' Matter? The Role of Social Capital on the Motivation to Donate Blood - Jaafar, Juliana Rosmidah; Chong, Sheau Tsuey; Alavi, Khadijah; Desa, Asmawati (UUM Press, 2019)
Social networking among blood donors is important in sustaining the intention to consistently donate blood on a voluntary basis. The interaction between blood donors who share the same interest might indirectly increase the possibility of blood donation in the future. Therefore, this study aims to investigate the role of social capital among blood donors as a moderator to understand the blood donors motivation and intention to donate. This study hypothesizes that Social Capital among Blood Donors (SCBD) increases motivational aspects (attitude, self-efficacy, subjective norms, anticipated regret, self-identity as blood donor, social awareness, and humanitarian) in blood donation. A number of 431 respondents, registered as blood donors at the National Blood Centre, Kuala Lumpur were recruited via random sampling. Data was collected using self-administered questionnaires. Results from correlation showed that all motivational aspects, except for subjective norm, were significantly correlated with the intention to donate blood. Meanwhile, results from the regression test reflected that forming social capital among blood donors could strengthen the blood donors attitude and the sense of social awareness, which in turn strengthen their intention to donate blood. This finding implies that blood donation campaigns need to highlight the aspect of social capital in the networking of blood donors, such as encouraging them to bring other people to donate blood. This could help to promote the significance of social capital among blood donors. Future researches need to pay attention to the role of social capital as a mechanism that influences the motivational aspects, which help to sustain the intention in volunteering activities.